Computed Tomography Enhancement Pattern of the Pancreatic Parenchyma Predicts Postoperative Pancreatic Fistula After Pancreaticoduodenectomy. Issue 2 (February 2019) - Maehira, Hiromitsu; Iida, Hiroya; Mori, Haruki; Kitamura, Naomi; Miyake, Toru; Shimizu, Tomoharu; Tani, Masaji
Abstract : Objective: The aim of this study was to assess the relationship between the computed tomography (CT) pancreatic parenchyma attenuation value and clinically relevant postoperative pancreatic fistula (POPF). Methods: The medical records of 115 patients who underwent pancreaticoduodenectomy and preoperative dynamic CT were retrospectively reviewed. The CT attenuation values of the nonenhanced (N), arterial (A), portal venous (P), and late (L) phase in the pancreatic parenchyma were determined via CT, and the A/N, A/P, and P/L ratios were calculated. The CT attenuation values and value ratios were compared between the POPF and non-POPF groups. Results: Thirty-two patients (28%) were categorized in the POPF group. On univariate analysis, the A/P ratio ( P < 0.001) and P/L ratio ( P = 0.018) were significantly higher in the POPF group. On receiver operating characteristic curve analysis, the A/P and P/L ratio cutoff values for predicting POPF were 1.19 and 1.17, respectively. Of the preoperative evaluable factors, A/P ratio of 1.19 or greater ( P < 0.001; odds ratio, 10.3) and P/L ratio of 1.17 or greater ( P = 0.049; odds ratio, 3.23) were independent predictive factors for POPF, and the combination of the 2 ratios was useful in detecting POPF preoperatively. Conclusions: The enhancement pattern of the pancreatic parenchyma is associated with the development of clinically relevant POPF.